MO027EVALUATING THE FEASIBILITY AND IMPACT OF A MOBILE PHONE TEXT MESSAGING INTERVENTION ON ADHERENCE TO DIETARY RECOMMENDATIONS IN PATIENTS ON HAEMODIALYSIS (KIDNEYTEXT). (6th June 2020) - Dawson, Jessica; Campbell, Katrina L; Craig, Jonathan; Tong, Allison; Teixeira-Pinto, Armando; Brown, Mark A; Howard, Kirsten; Howell, Martin; Khalid, Rabia; Sud, Kamal; Thiagalingam, Aravinda; Chow, Clara K; et al.
Abstract: Background and Aims: Nutritional management is an important, but complex, component of treatment for people on haemodialysis. Dietary recommendations are poorly adhered to, and novel strategies to improve self-management are needed. The aim of this study was to determine the feasibility and effectiveness of a mobile phone text message intervention to improve dietary behaviours in people on haemodialysis. Method: We conducted a six-month, multi-centre randomised controlled trial (2:1) in patients on maintenance haemodialysis. Participants who were randomised to receive the KIDNEYTEXT intervention received three semi-tailored text messages per week for six months plus usual care. The control group received usual care. The primary outcome was a composite outcome to determine feasibility, using: recruitment rate, retention rate, adherence to dietary recommendations and acceptability. Adherence to dietary recommendations was defined as meeting 3 of 4 nutrition guidelines (potassium, phosphorus, sodium and protein). Acceptability was evaluated by semi-structured interviews to elicit perspectives regarding satisfaction, acceptability and change in behaviours. Secondary outcomes included serum electrolytes, interdialytic weight gain (IDWG) and dietary intake. Trial registration - ACTRN12617001084370. Results: In total, 130 participants were recruited (87 intervention, 43 control) from six haemodialysis units in Sydney, Australia. 48% of eligible patients consented to participate and 114 participants (88%) completed the trial. Whilst there was no significant difference in adherence to dietary recommendations at 6 months (p=0.14), there were significant reductions in dietary intake of potassium (p=0.01), phosphorus (p=0.003), sodium (p=0.031) and protein (p=0.024) in intervention participants compared to control. Compared to control participants, intervention arm had a significant increase in the number of participants meeting IDWG guidelines (p=0.005) and significant reduction in average IDWG (p=0.024). There was a significant reduction in the number of phosphate binders prescribed in the intervention arm compared to control at 6 months (p=0.03). There was no significant difference in serum electrolytes between the 2 arms at 6 months. Semi-structured interviews explored acceptability, with 5 themes emerging: clear and comprehensive, engaging with consistent and relevant content, maintaining attention with timely reminders, sustaining interest through ongoing care and generic messages inadequate to prompt dietary change. Conclusion: A mobile phone text message intervention targeting dietary behaviours in people on haemodialysis is feasible and has the potential to change dietary behaviours and improve clinical parameters, such as fluid management and pill burden. Future trials evaluating the effect of a mobile phone text message intervention on patient-centred and clinical outcomes in the haemodialysis population is warranted.